CORRIGENDUM: ANAEROBIC BACTERIA ISOLATED FROM CLINICAL SPECIMENS IN A UNIVERSITY HOSPITAL AND RESISTANCE OF ANAEROBIC GRAM-NEGATIVE RODS TO ANTIBIOTICS - Lütfiye Öksüz (İstanbul Tıp Fakültesi Dergisi)
.